Evidence of Bank Market Discipline in Subordinated Debenture Yields: 1983-1991. - Flannery, Mark J; Sorescu, Sorin M (Journal of Finance, 1996)
The authors examine debenture yields over the period 1983-91 to evaluate the market's sensitivity to bank-specific risks and conclude that investors have rationally reflected changes in the government's policy toward absorbing private losses in the event of a bank failure. Although this evidence does not establish that market discipline can effectively control banking firms, it soundly rejects the hypothesis that investors cannot rationally differentiate among the risks undertaken by the major U.S. banking firms.